Firm-Specific Determinants of Share Price: Evidence from Nepalese Commercial Banks - Niraula, Damodar; Shilpakar, Jeshika; Shrestha, Sachet (The Batuk, 2026)
Empirical studies from emerging markets such as Nepal and other South Asian countries report inconsistent and often contradictory findings regarding firm-specific determinants of share prices. To address these issues, the researchers adopted a correlational and explanatory research design so as to examine the relationship and explanatory power of firm-specific determinants over market price per share (MPS) of Nepalese commercial banks. Sixteen commercial banks were selected using judgmental sampling, and balanced panel data covering 2019/20–2023/24 were collected from their annual reports. Ordinary least squares (OLS) regression revealed significant positive effects of cash reserve ratio (CRR), capital adequacy ratio (CAR), and total assets (TA) on MPS, while return on assets (ROA) showed a positive but non-significant effect. Conversely, weighted average interest rate spread (WAIRS), credit-to-deposit ratio (CDR), and non-performing loan ratio (NPLR) showed significant negative effects on MPS. These findings provide valuable insights for investors, helping them make more informed decisions.